If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -5 + -2t + 4 = 0 Reorder the terms: -5 + 4 + -2t + 6y = 0 Combine like terms: -5 + 4 = -1 -1 + -2t + 6y = 0 Solving -1 + -2t + 6y = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -2t + 1 + 6y = 0 + 1 Reorder the terms: -1 + 1 + -2t + 6y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2t + 6y = 0 + 1 -2t + 6y = 0 + 1 Combine like terms: 0 + 1 = 1 -2t + 6y = 1 Add '-6y' to each side of the equation. -2t + 6y + -6y = 1 + -6y Combine like terms: 6y + -6y = 0 -2t + 0 = 1 + -6y -2t = 1 + -6y Divide each side by '-2'. t = -0.5 + 3y Simplifying t = -0.5 + 3y
| 32x-22=-4(1-8x) | | 12b-2=7 | | s+2.5s+20=55 | | 2x=2x+2x | | 11+5q=12+4q | | 6(t+5)=5(1+t)-5 | | 7v=8.75 | | 4=-(p-5) | | -13(-8x+7)-3=14(x+19) | | f-v=f+yx | | 7(3+v)+34v=15v | | -2+11=m-6 | | 3(x-4)=8+7x | | 23+11+2c=10-2c | | 20x+5x=15 | | 1200+40x=3000 | | -2-7b=12 | | 18t^2+18-32t^3=0 | | 2(2x+3)+-2=5 | | -2b-7=12 | | 3(8m-13)+10=17(3+2m) | | 10+2m=16 | | 2(2x+3)-2=2 | | (x*x)-3x=0 | | -2-7=12 | | 1/5x+1/2=3/10x-1 | | a=bx+6x+d | | 4(-2+x)=5(x+.5) | | -3x+6-5=5x+4 | | 8c-9=47 | | 34x+5=175 | | 0=2x^2+11x-9 |